2021
DOI: 10.1080/00224499.2021.1897067
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sexual Desire and Behaviors among UK Young Adults During Social Lockdown Due to COVID-19

Abstract: This study examined self-reported changes in young adults' sexual desire and behaviors during the most significant social restrictions imposed to deal with COVID-19. Drawing on a survey of 565 British adults aged 18-32 collected at the peak of social lockdown restrictions, we document an overall decrease in sexual behaviors consistent with abiding by social restrictions. We found that the levels of sexual desire reported by women (but not men) decreased compared with reports of pre-lockdown levels. Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
90
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(103 citation statements)
references
References 45 publications
(41 reference statements)
10
90
3
Order By: Relevance
“…Our data empirically supports a positive relationship between sexting and opportunity. Similarly to previous literature, our results showed that there is an association between living alone and sexting engagement and that those who lived with a third party (friends, parents, partner) sexted less than those who lived by themselves, which is in line with other research [ 13 , 23 ]. The presence of the so-called capable guardians might discourage engagement in sexually-related activities, such as voluntary sexting, and might also discourage the perpetration of OSV [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data empirically supports a positive relationship between sexting and opportunity. Similarly to previous literature, our results showed that there is an association between living alone and sexting engagement and that those who lived with a third party (friends, parents, partner) sexted less than those who lived by themselves, which is in line with other research [ 13 , 23 ]. The presence of the so-called capable guardians might discourage engagement in sexually-related activities, such as voluntary sexting, and might also discourage the perpetration of OSV [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…It has also been reported that an increase in the frequency of internet use is strongly correlated with an increase in sexting engagement [ 11 ]. Furthermore, during the pandemic, sex with people outside the household posed a significant risk of SARS-CoV-2 transmission, so interpersonal sexual contact at a distance could be solved by technology-mediated sexual interactions [ 12 , 13 ]. In line with these findings, Ballester–Arnal et al reported that almost 50% of their adult Spanish sample increased their online sexual activities during the COVID-19 lockdown [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“… 26 , 27 Data were from 565 participants drawn from an anonymous, cross-sectional survey conducted to explore sexual health and wellbeing during social lockdown. 28 On average, participants were in their twenties ( = 25.41, SD = 4.15) who did not tend to self-isolate (69% no, 31% yes) and were not working as essential workers (78.6% no, 21.4% yes) at the time of data collection. Participants rated their perceived global health status on a scale of 1 ( poor ) to 5 ( excellent ), reporting above-average health ( M = 3.52, SD = 0.91).…”
Section: Methodsmentioning
confidence: 99%
“…The reason for the decrease in breasts and buttocks as targets of touch desire and touch awareness is unclear but it might be related to a decrease in sex drive. Recent studies have shown that women in the UK and men in Italy have a tendency for low libido during the lockdown and quarantine, respectively 24,25 . In fact, the number of acts of sexual intercourse has decreased during quarantine in Italy 25 .…”
Section: Discussionmentioning
confidence: 99%